2000
DOI: 10.1038/sj.ijo.0801223
|View full text |Cite
|
Sign up to set email alerts
|

Obesity indices in a cohort of primary school children in Crete: a six year prospective study

Abstract: OBJECTIVE: To report on the body mass index (BMI), waist-to-hip ratio (WHR) and sum of skinfolds in a cohort of Cretan children and identify the factors associated with these indices. DESIGN: The present study was a follow-up study. Children were measured prospectively at ages 6, 9 and 12. SUBJECTS: Pupils came from 40 schools randomly selected from the 541 primary schools in three different provinces of Crete. 1046 pupils were examined at age 6. At age 9, a representative sample from the original cohort (n 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
72
5
14

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 34 publications
11
72
5
14
Order By: Relevance
“…These prevalence rates are higher compared to those reported by other earlier studies conducted among children and adolescents in south (Mamalakis et al, 2000), central (Manios et al, 2004) and north districts of the Greek territory (Krassas et al, 2001b), as well as those reported for other developed countries (Chinn and Rona, 2001;Flegal et al, 2001;Ogden et al, 2002;Booth et al, 2003). Similarly, the prevalence of hypertension was found to be equally high, exceeding the rates reported for respective age groups in Greece (Bouziotas et al, 2004;Papadopoulou-Alataki et al, 2004) and other developed countries (McCarron et al, 2002).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…These prevalence rates are higher compared to those reported by other earlier studies conducted among children and adolescents in south (Mamalakis et al, 2000), central (Manios et al, 2004) and north districts of the Greek territory (Krassas et al, 2001b), as well as those reported for other developed countries (Chinn and Rona, 2001;Flegal et al, 2001;Ogden et al, 2002;Booth et al, 2003). Similarly, the prevalence of hypertension was found to be equally high, exceeding the rates reported for respective age groups in Greece (Bouziotas et al, 2004;Papadopoulou-Alataki et al, 2004) and other developed countries (McCarron et al, 2002).…”
Section: Discussioncontrasting
confidence: 54%
“…diet and physical activity) (Mamalakis and Kafatos, 1996;Krassas et al, 2001b;Magkos et al, 2005). The determinants of body mass index (BMI) and BP in Greek children and adolescents remain another understudied topic (Mamalakis et al, 2000;Krassas et al, 2001a;Manios et al, 2004). Furthermore, there are no data at all for the less privileged regions of Greece where the prevalence and trends of these clinical and behavioural CVD risk factors might be expected to be higher.…”
Section: Introductionmentioning
confidence: 99%
“…Our results on obesity rates are similar to those reported by Krassas et al (2001) for the area of Thessaloniki. On the other hand, significantly higher rates for overweight and obesity were observed in Cretan schoolaged children (Mamalakis et al, 2000). This difference may be because of methodological issues, namely the use of different cutoff points.…”
Section: Discussionmentioning
confidence: 94%
“…To the best of our knowledge, only two studies have investigated the prevalence of obesity among Greek children and adolescents (Mamalakis et al, 2000;Krassas et al, 2001). Their results are fragmentary, drawn from selected areas of Greece, and therefore not representative of the entire population.…”
Section: Introductionmentioning
confidence: 99%
“…The BMI of Cretan children and adults has been rising at an amazing rate over the last 30 y (Table 6), and obesity is now of great concern not only in adults but also in children (Mamalakis & Kafatos, 1996;Mamalakis et al, 2000). Recently Trichopoulou et al, (2000) published the first evidence on the BMIs of the Greek cohort of the EPIC study started in 1992 on a nation-wide sample of adult men (n ¼ 5633) and women (n ¼ 8648).…”
Section: Obesity Ratesmentioning
confidence: 99%